Overuse and Underuse of Visual Field Testing Over 15 Years. Issue 7 (July 2019) - Ben-Artsi, Elad; Goldenfeld, Modi; Zehavi-Dorin, Tzukit; Cohen, Asaf; Porath, Avi; Levkovitch-Verbin, Hani
Abstract : Précis: A 15-year analysis of 198, 843 visual field (VF) tests revealed a growing trend for their performance for nonglaucoma indications. Adherence to glaucoma management guidelines was suboptimal. Guidelines for referral to VF assessments should be established. Purpose: The purpose of this study was to identify trends in VF assessments over 15 years among patients with and without suspected or confirmed glaucoma, in a large healthcare maintenance organization. Methods: This was a population-based retrospective cohort study, conducted by means of electronic medical database analyses. Study population: Maccabi Healthcare Services is an healthcare maintenance organization that insures 2 million members constituting 25% of the population. All members who underwent at least 1 VF test between January 2000 and December 2014 were included. In addition, all members with glaucoma or suspected glaucoma diagnosis or who were prescribed with antiglaucoma medications were evaluated. Main outcome measures: VF performance rates. Results: A total of 93, 617 Maccabi Healthcare Services members underwent 198, 843 VF tests; of whom 47.9% involved patients without any glaucoma-related conditions. There was a growing trend over time toward more of those members to undergo VF tests and, by 2014, non–glaucoma-related members comprised 74.0% of new VF assessments. In contrast, 32.3% of glaucoma-related patients did not perform even 1 VF test throughout the entire study period. Although over 2 years (25.95±6.33 mo) passed between the first glaucoma-related diagnosis and first VF test, once a patient underwent the first VF test, an average once-a-year VF follow-up (0.95±0.37 annual tests) began. Conclusion: There is a growing trend for VF tests being apparently overused for indications other than glaucoma. Concurrently, adherence to glaucoma management guidelines on VF tests is suboptimal, leading to discernible underuse. Guidelines for VF assessments in nonglaucoma patients should be established. Adherence to existing glaucoma management guidelines should be improved. Abstract : Supplemental Digital Content is available in the text.